Act of betrayal - Buchanan, Edna. (New York : Hyperion, 1996)
A fatal bomb blast propels police reporter Britt Montero into the story of her life, as Britt probes the baffling case, an old mystery reopens personal wounds.
Kirkus Review.
New York Times.
Wilson's Fiction.
Adult
Keywords: Montero, Britt (Fictitious character) -- Fiction; Women journalists -- Florida -- Miami -- Fiction; Montero, Britt (Fictional character) -- Fiction; Mystery fiction; Women journalists -- Fiction; Miami (Fla.) -- Fiction; Miami (Fla.) -- Fiction; Detective and mystery stories